Human rights of imprisoned women in the situation of vulnerability to STD-Aids - Giordani, Annecy T.; Bueno, Sônia M.V. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Background: Imprisoned women have suffered from omission and power abuse, which leads to rebellion and dissemination of STD-Aids in and out ofprisons. Included in a ruined prison system, their Human Rights are effectively disrespected. Objectives: To investigate how authorities view theapplication of Human Rights in prison environments and identify the major aspects concerning such reality as to the quality of life of a female prisoners. Methods: A qualitative and humanistic action research was developed by using an open questionnaire sent by mau to 5 subjects, of whom 3 were chiefpolice offlcers and 2 were lawyers. Results: The answers from the chief police officers opposed those from lawyers. As to the dissemination of diseases suchas aids and STD among prisoners, there was a unanimous opinion when mentioning sexual promiscuity in prisons; precanous actions for aids, DST anddrug control as well as the need for implementation of preventive educational programs for STD-aids and drugs aiming at prisoners. Conclusions: It wasconcluded that there is an urgent need to reverse the present situation through the refonnulation of the existing prison system, since the increasing numberof women contaminated by HIV in Brazil and the lack of educational programs for STD-aids are alarming, particularly in small and medium-sized Brazilianprisons such as public prisons for females.